Design and Optimization of Permanent Magnet Brushless Machines for Electric Vehicle Applications - Weiwei Gu; Xiaoyong Zhu; Li Quan; Yi Du (Energies, 2015)
In this paper, by considering and establishing the relationship between the maximum operating speed and d-axis inductance, a new design and optimization method is proposed. Thus, a more extended constant power speed range, as well as reduced losses and increased efficiency, especially in the high-speed region, can be obtained, which is essential for electric vehicles (EVs). In the first step, the initial permanent magnet (PM) brushless machine is designed based on the consideration of the maximum speed and performance specifications in the entire operation region. Then, on the basis of increasing d-axis inductance, and meanwhile maintaining constant permanent magnet flux linkage, the PM brushless machine is optimized. The corresponding performance of the initial and optimal PM brushless machines are analyzed and compared by the finite-element method (FEM). Several tests are carried out in an EV simulation model based on the urban dynamometer driving schedule (UDDS) for evaluation. Both theoretical analysis and simulation results verify the validity of the proposed design and optimization method.